2023
DOI: 10.3389/fmed.2023.1029021
|View full text |Cite
|
Sign up to set email alerts
|

The mammalian target of rapamycin contributes to synovial fibroblast pathogenicity in rheumatoid arthritis

Abstract: ObjectivesThe mammalian target of Rapamycin (mTOR) is a metabolic master regulator of both innate and adaptive immunity; however, its exact role in stromal cell biology is unknown. In this study we explored the role of the mTOR pathway on Rheumatoid Arthritis synovial fibroblast (RASF) metabolism and activation and determined if crosstalk with the Hippo-YAP pathway mediates their effects.MethodsPrimary RA synovial fibroblasts (RASF) were cultured with TNFα alone or in combination with the mTOR inhibitor Rapamy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 49 publications
1
7
0
Order By: Relevance
“…The role of the crosstalk between mTOR and the Hippo-YAP pathways in mediating RASF invasive mechanism was demonstrated. Here, Rapamycin abrogated YAP expression, and YAP inhibition inhibited RASF invasiveness [27] showing that multiple pathways contribute to the invasion of RASF into cartilage. Another study showed that PU.1, a central regulator of the pro-fibrotic system, led to hyper-activation and an inflammatory status of not only RASF but also of macrophages, whereas FMS-like tyrosine kinase 3 (FLT3) showed opposite effects [28].…”
Section: Rheumatoid Arthritis Synovial Fibroblasts Are Activated By P...mentioning
confidence: 92%
See 1 more Smart Citation
“…The role of the crosstalk between mTOR and the Hippo-YAP pathways in mediating RASF invasive mechanism was demonstrated. Here, Rapamycin abrogated YAP expression, and YAP inhibition inhibited RASF invasiveness [27] showing that multiple pathways contribute to the invasion of RASF into cartilage. Another study showed that PU.1, a central regulator of the pro-fibrotic system, led to hyper-activation and an inflammatory status of not only RASF but also of macrophages, whereas FMS-like tyrosine kinase 3 (FLT3) showed opposite effects [28].…”
Section: Rheumatoid Arthritis Synovial Fibroblasts Are Activated By P...mentioning
confidence: 92%
“…mTOR (mammalian target of Rapamycin), a metabolic regulator of innate and adaptive immunity, was evaluated regarding RASF activation and invasive properties [27]. RASF after TNF stimulation showed higher phosphorylation of S6 (a downstream target of mTOR) and were responsive to mTOR inhibition via Rapamycin.…”
Section: Rheumatoid Arthritis Synovial Fibroblasts Are Activated By P...mentioning
confidence: 99%
“…74,80,160 Still, the mechanisms involved in RA-FLS phenotype alteration remain to be elucidated. Recent literature has reported increased expression of YAP/TAZ in synovium in both antigen-induced arthritis (AIA) mice and RA patients, 79,160,161 and enriched epigenetic modifications of the YAP/TAZ were found in RA-FLS compared to OA-FLS. 78,80 These results suggest that YAP/TAZ might function as an important pathogenic regulator in RA-FLS.…”
Section: Yap/taz and Ramentioning
confidence: 99%
“…The typical features of RA are synovial inflammation and the concomitant destruction of adjacent cartilage and bone, and evidence is accumulating that FLSs play a pivotal role in this process 34,76,158,159 . FLSs are one of the primary pathological cell types within the RA joint, which acquire an aggressive phenotype and promote inflammation when RA progresses 74,80,160 . Still, the mechanisms involved in RA‐FLS phenotype alteration remain to be elucidated.…”
Section: Effects Of Yap/taz On Arthritismentioning
confidence: 99%
“…118 Researchers have also shown that rapamycin regulates genes in the Hippo-YAP pathway, which are predicted to converge with the mTOR pathway, in RA synovial tissue. 119 These activities ultimately alter rheumatoid arthritis synovial fibroblast metabolism and inhibit glycolysis and the expression of rate-limiting glycolytic enzymes in human synovial fibroblasts. 119 Bottini et al 72,120 reported that drugs aimed at decreasing the expression of YAP and nuclear YAP in FLS could inhibit the migration, invasion and inflammatory activity of FLS and ameliorate arthritis severity.…”
Section: Atdc Cellsmentioning
confidence: 99%